(3TQM GdCSHGH hGdYdGeGJ ddSeQbfOis - (3HQgGf GdOjf fajS Hf YhV Hf Mcje GdcQeGfis; (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3eMehO Hf ejQ CMeO GdJHQjRi s)
(3ChdgG (B:s
(3hHYO ,ajbhd GdYHO GdabjQ hcGf bSe GdWH ef gPG Gdaf de jbUO CMO GdCaGVd Edi GdBf dJaSjQg hJTQjMg aCQOJ Cf CcTa Yf hLhg ahGFO gPG Gdaf bGd GdeUfa GdUOGY Cde s
(3BNQgG (B:s
(3hCf jbJUQ Ydi eKd LhR GdSQh hGdCHgd , hSGFQ eG jfaY ai VeGO GdaJb , aEfgG JTO GdYVh hJfTa GdQWhHGJ hGddg CYde s
(3hbO ETJgQ cJGH GdCSHGH hGdYdGeGJ dfLjH GdOjf eMeO Hf Ydi GdSeQbfOi GdeJhai (B619 (3HSHH TQM fajS Hf YhV Ydjg hgh dWja eeRhL Mbb ajg aCLGOs
(3Cdag ddSdWGf CejQ RGOg haQZ ef JCdja SfI (B827(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdWHs